2021
DOI: 10.3390/antiox10010083
|View full text |Cite
|
Sign up to set email alerts
|

Role of Phytochemicals in Perturbation of Redox Homeostasis in Cancer

Abstract: Over the past few decades, research on reactive oxygen species (ROS) has revealed their critical role in the initiation and progression of cancer by virtue of various transcription factors. At certain threshold values, ROS act as signaling molecules leading to activation of oncogenic pathways. However, if perturbated beyond the threshold values, ROS act in an anti-tumor manner leading to cellular death. ROS mediate cellular death through various programmed cell death (PCD) approaches such as apoptosis, autopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 149 publications
0
19
0
Order By: Relevance
“…Medicinal plants have made a significant contribution to the rapidly expanding discipline of natural product chemistry. Natural products have also been accepted as a significant source in satisfying the healthcare demands of many societies, as a result of several discoveries [9]. Hence, natural products are part of current and effective tools for developing novel pharmaceuticals, as well as a bank of pharmacological templates [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal plants have made a significant contribution to the rapidly expanding discipline of natural product chemistry. Natural products have also been accepted as a significant source in satisfying the healthcare demands of many societies, as a result of several discoveries [9]. Hence, natural products are part of current and effective tools for developing novel pharmaceuticals, as well as a bank of pharmacological templates [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that there are higher levels of oxidative stress in cancer cells compared to normal cells due to their hypermetabolic state, which also disrupts cell death signaling, and causes drug resistance. Higher levels of oxidative stress enhance cancer cell survival, proliferation, angiogenesis, and metastasis [ 78 , 79 ]. Despite its tumorigenesis effect, this altered biochemical behavior of cancer cells can be exploited to yield therapeutic benefits.…”
Section: Effect Of Det and Idet On Apoptosis Pathwaysmentioning
confidence: 99%
“…Cellular organelles and macromolecules, such as DNA, lipids, and proteins, under excessive oxidative stress experience oxidative damage, leading to cell death. Several in vitro and in vivo studies have shown that ROS-generating phytochemicals could pose oxidative damage, therefore selectively cause apoptosis of cancer cells by ROS-mediated mechanisms [ 78 , 79 , 80 ].…”
Section: Effect Of Det and Idet On Apoptosis Pathwaysmentioning
confidence: 99%
“…Natural phytochemicals have been applied to the therapy of various diseases, including tumors (8). These phytochemicals can effectively inhibit the initiation, development and progression of neoplasm by regulating cellular proliferation, apoptosis and metastasis (9). Recent studies have indicated the important roles of natural compounds in modulating tumor angiogenesis by promoting the apoptosis of endothelial cell and inhibiting the angiogenesis-associated cytokines (10).…”
Section: Introductionmentioning
confidence: 99%